2023
DOI: 10.1101/2023.01.26.525651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wengen, a Tumour Necrosis Factor Receptor, regulates the Fibroblast Growth Factor pathway by an unconventional mechanism

Abstract: Unveiling the molecular mechanisms of receptor activation has led to much understanding of development as well as the identification of important drug targets. We use the Drosophila tracheal system to study the activity of two families of widely used and conserved receptors, the TNFRs and the RTK-FGFRs. Breathless, an FGFR, is known to respond to ligand by activating the differentiation program of the tracheal terminal cell. Here we show that Wengen, a TNFR, acts independently of both its canonical ligand and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 48 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…S1, B to E). The observation that the majority of Wgn is localized in intracellular vesicles rather than at the plasma membrane is consistent with our previous observations in larval epithelia and a recent study in the embryonic tracheal system (11,12). To test whether TNFR signaling regulates energy homeostasis in homeostatic conditions, we quantified lipid levels in wgn and grnd null mutant guts.…”
Section: Wgn/tnfr Restricts Lipid Catabolism Independently Of Its Lig...supporting
confidence: 87%
See 2 more Smart Citations
“…S1, B to E). The observation that the majority of Wgn is localized in intracellular vesicles rather than at the plasma membrane is consistent with our previous observations in larval epithelia and a recent study in the embryonic tracheal system (11,12). To test whether TNFR signaling regulates energy homeostasis in homeostatic conditions, we quantified lipid levels in wgn and grnd null mutant guts.…”
Section: Wgn/tnfr Restricts Lipid Catabolism Independently Of Its Lig...supporting
confidence: 87%
“…A recent study showed that Wgn localizes to late endosomes and lysosomes in the embryonic tracheal network, where it acts independently of Egr to promote degradation of the FGFR receptor, Breathless (Btl), and repress terminal cell differentiation (11). Intriguingly, the authors show that knockdown of Wgn results in the accumulation of Btl and its ligand, branchless (Bnl), in intracellular vesicles, suggesting that Wgn restricts Bnl/Btl signaling by preventing their accumulation in intracellular vesicles (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Egr employs Grnd to mediate JNK-dependent proapoptotic responses, its activation of Wgn stimulates prosurvival behaviors and cytoprotective processes to combat infections and promote tissue healing ( [15,16,50]; see below). Although the localization of Wgn in endosomes seems at odds with its function as a receptor for Egr, a fraction of Wgn is detected at the membrane upon forced expression, suggesting that it might be transiently available for ligand interaction [53]. Interestingly, in certain conditions, TNFRs are activated in ligand-independent fashions.…”
Section: Initiation Of Tnf-tnfr Signalingmentioning
confidence: 99%
“…Hence, Wgn controls developmental photoreceptor axon targeting through its association with the ezrin/radixin/moesin (ERM) family member, moesin, a process that does not depend on Egr [52]. In addition, as discussed in more detail below, Egr-independent functions of Wgn in regulating protein stability to restrict lipid catabolism in the gut and tracheal terminal cell differentiation are starting to emerge [50,53]. Likewise, knockdown of the Avalanche (Avl), a syntaxin required for an early step of endocytosis, results in JNK-driven neoplastic overgrowth, a process that does not require Egr [10].…”
Section: Initiation Of Tnf-tnfr Signalingmentioning
confidence: 99%

ROS-mediated TNFR Wengen activation in response to apoptosis

Esteban-Collado,
Fernàndez-Mañas,
Fernández-Moreno
et al. 2023
Preprint